Atrial septal aneurysm with rare comorbid pulmonary arteriovenous malformation as aetiology for cryptogenic stroke. Issue 6 (26th June 2019) - Bell, Kendall; Abu-Heija, Ahmad; Smith, Antonio; Nnodim, Ijeoma
Abstract : Atrial septal aneurysms have two mechanisms for cardioembolic events. One is the aneurysm itself can act as a nidus for thrombus formation in the left atrium. The aneurysm creates an area of low turbulence leading to haemostasis allowing fibrin-platelet adhesions to form. If the clot is on the left atrial wall, it may be dislodged by oscillations of the septum and travel into the systemic circulation. The second mechanism is via, an often comorbid, interatrial shunt such as a Patent Foramen Ovale or Atrial Septal Defect. We report a unique case where the associated right to left shunt leading to the cryptogenic stroke is a pulmonary arteriovenous malformation.